2017
DOI: 10.1038/bjc.2017.191
|View full text |Cite
|
Sign up to set email alerts
|

Impact of novel miR-145-3p regulatory networks on survival in patients with castration-resistant prostate cancer

Abstract: Background:Despite recent advancements, metastatic castration-resistant prostate cancer (CRPC) is not considered curative. Novel approaches for identification of therapeutic targets of CRPC are needed.Methods:Next-generation sequencing revealed 945–1248 miRNAs from each lethal mCRPC sample. We constructed miRNA expression signatures of CRPC by comparing the expression of miRNAs between CRPC and normal prostate tissue or hormone-sensitive prostate cancer (HSPC). Genome-wide gene expression studies and in silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
167
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 98 publications
(171 citation statements)
references
References 62 publications
1
167
3
Order By: Relevance
“…Based on our original miRNA expression signatures, including that for RCC, we have identified RNA networks that are controlled by anti‐tumor miRNAs in several cancers . Downregulation of the miR‐29 family ( miR‐29a , miR‐29b and miR‐29c ) was frequently observed in many types of cancers .…”
Section: Introductionmentioning
confidence: 99%
“…Based on our original miRNA expression signatures, including that for RCC, we have identified RNA networks that are controlled by anti‐tumor miRNAs in several cancers . Downregulation of the miR‐29 family ( miR‐29a , miR‐29b and miR‐29c ) was frequently observed in many types of cancers .…”
Section: Introductionmentioning
confidence: 99%
“…For example, miR-26a, miR-26b, miR-218, the miR-29-family, and miR-223 were downregulated in naive PCa tissues and these miRNAs inhibited cancer cell migration and invasion through targeting of genes involved in the extracellular matrix [27][28][29][30]. More recently, we showed that passenger strands of miRNAs, e.g., miR-150-3p and miR-145-3p acted as antitumor miRNAs in naive PCa and CRPC [18,31]. Interestingly, genes targeted by these miRNA passenger strands (SPOCK1, MELK, NCAPG, BUB1, and CDK1) were overexpressed in naive PCa and CRPC specimens and high expression of these genes predicted poor survival in patients with PCa [18].…”
Section: Discussionmentioning
confidence: 91%
“…More recently, we showed that passenger strands of miRNAs, e.g., miR-150-3p and miR-145-3p acted as antitumor miRNAs in naive PCa and CRPC [18,31]. Interestingly, genes targeted by these miRNA passenger strands (SPOCK1, MELK, NCAPG, BUB1, and CDK1) were overexpressed in naive PCa and CRPC specimens and high expression of these genes predicted poor survival in patients with PCa [18]. Analyses of our signatures revealed that miR-205-5p was significantly downregulated in naive PCa and CRPC specimens [16,17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations